Laboratory testing of extravascular body fluids : national recommendations on behalf of the Croatian Society of Medical Biochemistry and Laboratory Medicine : part II : synovial fluid - Jokić, Anja (Array, 2020)
Joint diseases are conditions with an often progressive and generally painful nature affecting the patient’s quality of life and, in some cases, requiring a prompt diagnosis in order to start the treatment urgently. Synovial fluid (SF) laboratory testing is an important part of a diagnostic evaluation of patients with joint diseases. Laboratory testing of SF can provide valuable information in establishing the diagnosis, be a part of a patient’s follow-up and treatment with the purpose of improving the patient’s health and quality of life. Synovial fluid laboratory testing is rarely performed in Croatian medical biochemistry laboratories. Consequently, procedures for SF laboratory testing are poorly harmonized. This document is the second in the series of recommendations prepared by the members of the Working group for extravascular body fluid samples of the Croatian Society of Medical Biochemistry and Laboratory Medicine. It addresses preanalytical, analytical, and postanalytical issues and the clinical significance of tests used in SF laboratory testing with the aim of improving the value of SF laboratory testing in the diagnosis of joint diseases and assisting in the achievement of national harmonization. It is intended for laboratory professionals and all medical personnel involved in synovial fluid collection and testing.